A general mathematical programming approach for process plant layout - Georgiadis, Michael C.; Schilling, Gordian; Rotstein, Guillermo E.; Macchietto, Sandro (Computers & chemical engineering, 1999)
The generation of a good layout is an important stage in the design of a new plant or the retrofit of an existing facility. Layout decisions affect piping, electrics, instrumentation and therefore have a great impact on the total plant cost. Moreover, layout has a large impact on the safety, operability and maintainability of any chemical plant. This paper presents a general mathematical programming approach for addressing the problem of allocating items of equipment in a given two or three dimensional space. The problem is formulated as a mixed integer linear programming model where equipment of various sizes and geometries are taken into account. The objective function to be minimized accounts for the total transport, connection, land and floor construction cost. This optimization procedure results in the coordinates of each unit (location), the total piping length, and the land occupied. Three case studies are presented to illustrate the applicability of the proposed approach.